Calibration Of Prototype "Ultrasonic Surface Roughmeter" With GAP Man Profilometer - Eko Wahyu Utomo; Pratikso Pratikso; Siegfried Siegfried (Eduvest - Journal of Universal Studies, 2024)
In road network evaluations, road performance is assessed from structural and functional aspects. Typically, road surface roughness measurements rely on expensive, imported instruments. Therefore, this research developed a prototype roughness measuring tool using an ultrasonic sensor, which is more cost-effective. This study aims to calibrate the "Ultrasonic Surface Roughmeter" prototype and evaluate its accuracy in measuring the International Roughness Index (IRI) as a reference for road maintenance. The prototype was tested through calibration with the standard tool, Gap Man Working Profilometer. Data were collected from several road segments of a specified length, and measurement results were analyzed through descriptive statistics to compare data from both tools. The calibration results indicate that the prototype achieved a high accuracy level, with a correlation value of 99.51% and a confidence level of 97.05%. The Cronbach's alpha value of 1.0 shows excellent internal consistency, with an average measurement difference of approximately 3.11%.The "Ultrasonic Surface Roughmeter" prototype can serve as a valid and economical alternative for measuring road surface roughness